Application of Therapeutic Nanoplatforms as a Potential Candidate for the Treatment of CNS Disorders: Challenges and Possibilities - Sa, Pratikshya; Singh, Priya; Dilnawaz, Fahima; Sahoo, Sanjeeb K. (Current Pharmaceutical Design, 2022)
Drug delivery to central nervous system (CNS) diseases is one of the most challenging tasks. The innate blood-brain barrier (BBB) and the blood-cerebrospinal fluid (BCSF) barrier create an obstacle to effective systemic drug delivery to the CNS, by limiting the access of drugs to the brain. Nanotechnology-based drug delivery platform offers a potential therapeutic approach for the treatment of neurological disorders. Several studies have shown that nanomaterials have great potential to be used for the treatment of CNS diseases. The nanocarriers have simplified the targeted delivery of therapeutics into the brain by surpassing the BBB and actively inhibiting the disease progression of CNS disorders. The review is an overview of the recent developments in nanotechnology-based drug delivery approaches for major CNS diseases like Alzheimer's disease, Parkinson's disease, ischemic stroke, and Glioblastoma. This review discusses the disease biology of major CNS disorders describing various nanotechnology-based approaches to overcome the challenges associated with CNS drug delivery, focussing on nanocarriers in preclinical and clinical studies for the same. The review also sheds light on the challenges during clinical translation of nanomedicine from bench to bedside. Conventional therapeutic agents used for the treatment of CNS disorders are inadequate due to their inability to cross BBB or BCSF, higher efflux from BBB, related toxicity, and poor pharmacokinetics. The amalgamation of nanotechnology with conventional therapeutic agents can greatly ameliorate the pharmacokinetic problems and at the same time assist in efficient delivery to the CNS.
Keywords: Nanotechnology